CRITICAL DISCOURSE ANALYSIS OF “TRANSBOUNDARY HAZE POLLUTION” ON DETIK.COM AND MALAYSIAKINI.COM NEWS PORTAL - Ujang Asmara; Deddy Mulyana; Henny Srimulyani Rohayati (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2020)
This study aimed to determine the construction of cross-border smoke haze (Transboundary Haze Pollution) on detik.com and malaysiakini.com news portal. This study used qualitative method with critical discourse analysis (Critical Discourse Analysis/ CDA) from Teun A. van Dijk’s Model. The results of this study showed that both the reporters detik.com and malaysiakini.com thematically used certain language prominence in writing the news. That was done to attract the attention of the readers. From these two different news portals, it could be concluded that each media was influenced by the interest of each country. It was also very clear that each media did not want to blame the state itself and pro-government. Schematically, from the beginning, detik.com reporters directed that Malaysia corner Indonesia not only through the issue of fog but also touched on the issue of the invasion of pigs. Whereas in the news portal malaysiakini.com, the journalist had directed the reader to the protest letter posted by Malaysia to the Indonesian government. While, semantically, detik.com reporters saw that Malaysia truly blames Indonesia without looking at companies from their countries which involved in forest and land fires in the Indonesian territory. On the malaysiakini.com portal, they dismissed it by making a phrase wanting to help the Indonesian government in dealing with fires that occurred in Indonesian territory.